log(8x-3)-log(x-3)=1

Simple and best practice solution for log(8x-3)-log(x-3)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(8x-3)-log(x-3)=1 equation:


Simplifying
log(8x + -3) + -1log(x + -3) = 1

Reorder the terms:
glo(-3 + 8x) + -1log(x + -3) = 1
(-3 * glo + 8x * glo) + -1log(x + -3) = 1
(-3glo + 8glox) + -1log(x + -3) = 1

Reorder the terms:
-3glo + 8glox + -1glo(-3 + x) = 1
-3glo + 8glox + (-3 * -1glo + x * -1glo) = 1
-3glo + 8glox + (3glo + -1glox) = 1

Reorder the terms:
-3glo + 3glo + 8glox + -1glox = 1

Combine like terms: -3glo + 3glo = 0
0 + 8glox + -1glox = 1
8glox + -1glox = 1

Combine like terms: 8glox + -1glox = 7glox
7glox = 1

Solving
7glox = 1

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '7lox'.
g = 0.1428571429l-1o-1x-1

Simplifying
g = 0.1428571429l-1o-1x-1

See similar equations:

| 6sin(2x)=0 | | -3(-5x-8)=144 | | 7xsquared+8x+1=0 | | y=500x+2250 | | -5+4u=-17 | | 3(9x-4)= | | 8c=4e-16 | | 7(3x-6)=126 | | 7x=448 | | y=0.2122x+15.21 | | -1=-7+3w | | 10x-10=-11x-20 | | x+25=x^2+6x+9 | | 3y^2-6y=24 | | -60=4(-3x-3) | | -2(x-5)=(2-1/2x)6 | | 360=(38x+5)+(21-2) | | 22x=440 | | -2(x-5)=-2(x-5) | | 360=(38x+5)+(21+-2) | | -8+5v=-43 | | 2(5-3x)=11+3x | | 33=8x-x-128 | | 2x^2=15+27 | | k^6+81k^4=0 | | 3(x-2)+5=2-3(2x+1) | | -5x+4(-x-9)=54 | | y^5-64y^3=0 | | -21=3y-6 | | 1/2y+5=12 | | 144x^2-9y^2= | | -31=4+5u |

Equations solver categories